Pengaruh Kombinasi Pupuk Organik Cair Termodifikasi Silika dan Varietas Terhadap Produktivitas Bawang Merah (Allium ascalonicum L.): The Combination Effects of Silica Modified Liquid Organic Fertilizer and Varieties on Shallot Productivity (Allium ascalonicum L.) - Sholihah, Sofi Marwatus; Hamawi, Mahmudah (Gontor Agrotech Science Journal, 2024)
Shallot plants (Allium ascalonicum L.) have short roots and soft leaves, potentially susceptible to environmental stress and pest attacks. Fulfillment of nutrients and variety selection as an alternative in increasing shallot production. The research aims to determine the effect of liquid organic fertilizer (LOF) modified silica (Si) and varieties on the productivity of shallot plants. The research was carried out at the Universitas Darussalam Gontor experimental field from November 2023 to January 2024. The research used a split-plot design with 2 factors. First factor: POC modified Si, P1 = POC 5 ml + Si 5 g.l-1, P2 = POC 10 ml + Si 5 g.l-1, P3 = without fertilizer (control). Second factor: variety, V1 = Bima Brebes, V2 = Thailand. Observation parameters were plant height, number of leaves, number of tillers, tuber diameter, wet and dry weight of tubers per plot (1 m-2), and wet and dry weight of the entire plant per plot (1 m-2). The observation data were analyzed using ANOVA and then tested further with 5% BNT. POC 5 ml + Silica 5 g.l-1 treatment increased the number of leaves, tillers, and wet and dry weight of shallot bulbs. The Bima Brebes variety has better plant height and diameter than the Thailand variety which is significantly different, while the number of tillers for the Thailand variety is greater. The Bima Brebes variety fertilized with POC 5 ml + Silica 5 g.l-1 increased the entire shallot plant's wet and dry weight (total bulbs and leaves).